(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In accordance with the State Program of Education Development for 2011-2020, it is supposed to transit to the 12-year education model in the secondary schooling of the republic, which calls for the creation of new textbooks for such schools. The paper considers the educational material about the typology of texts contained in the EMC for the Russian language for the experimental 11-th grade of the 12-year model of education. It analyzes the peculiarities of constructing such types of speech as polylogue, dialogue, monologue, it explains the meaning of the terms «verbal» (linguistic) and «non-verbal» (non-linguistic: facial expressions, gestures, intonation) means of communication. It considers elliptical constructions in certain types of texts, as well as tiered assignments for a corrective course of orthology and stylistics.